Growth and endocrine function after renal transplantation. Issue 11 (November 1988) - Rees, L; Greene, S A; Adlard, P; Jones, J; Haycock, G B; Rigden, S P; Preece, M; Chantler, C
Abstract : Longitudinal height data and physical development were assessed in 45 boys and 34 girls after renal transplantation. All children received alternate day steroids and either azathioprine or cyclosporin A for immunosuppression. There was a significant increase in growth velocity after transplantation in prepubertal children. Growth velocity declined at the expected age of the normal pubertal growth spurt, however, with delay in the appearance of secondary sexual characteristics. Overnight hormone profiles in 17 adolescent subjects with short stature or maturational delay, or both, showed blunting of growth hormone and gonadotrophin pulsatility. It is likely that long term steroid treatment after renal transplantation induces the clinical and endocrine picture of delayed puberty. Failure of growth to accelerate at this time is a cause of short stature, which may have an effect on adult height.